2018
DOI: 10.3390/molecules23102463
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer and Differentiation Properties of the Nitric Oxide Derivative of Lopinavir in Human Glioblastoma Cells

Abstract: Glioblastoma (GBM) is the most frequent and deadly form of primary malignant brain tumor among adults. A promising emerging approach for GBM treatment may be offered from HIV protease inhibitors (HIV-PIs). In fact, in addition to their primary pharmacological activity in the treatment of HIV infection, they possess important anti-neoplastic effects. According to previous studies, the addition of a nitric oxide (NO) donating group to parental compounds can reduce their toxicity and enhance the anticancer action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 58 publications
0
29
0
Order By: Relevance
“…It is also worth noting that the biological function of MIF can be inhibited by nitrosylation [72], and hence nitric oxide (NO) donors may indirectly promote MIF inhibition. Along these lines, we propose that together with NO-NSAID, that have been proven effective in both preclinical and clinical settings [73,74], and also other NO-donors such as the recently characterized lopinavir-NO and ritonavir-NO [75][76][77][78], deserve consideration as drugs to be used in the treatment of AD patients. These drugs NO donors could combine beneficial anti-inflammatory properties along with beneficial effects of NO on vascular conditions associated with AD.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth noting that the biological function of MIF can be inhibited by nitrosylation [72], and hence nitric oxide (NO) donors may indirectly promote MIF inhibition. Along these lines, we propose that together with NO-NSAID, that have been proven effective in both preclinical and clinical settings [73,74], and also other NO-donors such as the recently characterized lopinavir-NO and ritonavir-NO [75][76][77][78], deserve consideration as drugs to be used in the treatment of AD patients. These drugs NO donors could combine beneficial anti-inflammatory properties along with beneficial effects of NO on vascular conditions associated with AD.…”
Section: Discussionmentioning
confidence: 99%
“…We also studied the possible diagnostic and prognostic value of TSPAN32 expression in PBMC of MS patients, on the course of the disease. The use of whole-genome expression databases has been largely exploited [25][26][27][28] for the characterization of pathogenic pathways and to identify therapeutic targets for a variety of disorders, including immunoinflammatory and autoimmune diseases [29][30][31][32][33][34][35][36], cancer [37][38][39], and has allowed dismantling pathogenetic pathways [40][41][42], along with the identification of novel tailored therapeutic targets [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been found that nitrosylation could dampen MIF activity [108]. Hence, another possible interesting approach may be to use nitric oxide (NO)-hybridized drugs, such as NO-aspirin or NO-hybridized antiretroviral protease inhibitors, including lopinavir-NO [87,92,94,95] and ritonavir-NO [87,93], for the treatment of NB and eventually other diseases in which MIF is involved.…”
Section: Discussionmentioning
confidence: 99%
“…DNA microarray analysis is a widely used technique that helps to identify diagnostic tools, pathogenetic pathways, and novel cellular and pharmacological therapeutic targets in several types of pathologies including immunoinflammatory and autoimmune diseases [85][86][87][88][89][90], neurodegenerative diseases [91], and cancer [92][93][94][95] and allows identification of potential cellular and molecular therapeutic targets [96,97].…”
Section: In Silico Analysis Of Mif and Ddt In Nb As Potential Theranomentioning
confidence: 99%